Sami traditions: Márkomeannu`s contribution to the revitalization of Sami food traditions - Berg, Elisabeth (UiT Norges arktiske universitet, 2014)
This thesis focuses on the Márkomeannu festival’s contribution to the revitalization of food traditions. The study was conducted on the Márkomeannu festival in Skånland in Troms County, specifically in the Markasami areas in the rural hills of Skånland. The festival was chosen because it is an important arena for expression of indigeneity and culture. Many areas within the Sami community have suffered from assimilation and have afterwards gone through a process of revitalization. The process of revitalization of the culture, language, politics and history has been thoroughly studied and written about, but the revitalization of Sami traditional food has not been studied in detail. Food is an important cultural marker which works as building stones of each cultural foundation. Food can be both symbolic and be a purely practical necessity for a culture. The thesis establishes that some traditional dishes are adopted and adapted from international dishes. The results shows that traditional dishes are used to articulate the Sami culture, and that traditions can be adapted to a modern outlook, and also adapted to fit a Sami cultural profile. Márkomeannu as a cultural arena contributes to revitalization of food by creating a platform for cultural expression which can lead to a stronger Sami identity and a feeling of safety in expressing culture.